An ankylosing spondylitis-associated genetic variant in the IL23R-IL12RB2 intergenic region modulates enhancer activity and is associated with increased Th1-cell differentiation. Issue 12 (25th February 2016) - Roberts, Amity R; Vecellio, Matteo; Chen, Liye; Ridley, Anna; Cortes, Adrian; Knight, Julian C; Bowness, Paul; Cohen, Carla J; Wordsworth, B Paul
Abstract : Objectives: To explore the functional basis for the association between ankylosing spondylitis (AS) and single-nucleotide polymorphisms (SNPs) in the IL23R - IL12RB2 intergenic region. Methods: We performed conditional analysis on genetic association data and used epigenetic data on chromatin remodelling and transcription factor (TF) binding to identify the primary AS-associated IL23R-IL12RB2 intergenic SNP. Functional effects were tested in luciferase reporter assays in HEK293T cells and allele-specific TF binding was investigated by electrophoretic mobility gel shift assays. IL23R and IL12RB2 mRNA levels in CD4+ T cells were compared between cases homozygous for the AS-risk 'A' allele and the protective 'G' allele. The proportions of interleukin (IL)-17A+ and interferon (IFN)-γ+ CD4+ T-cells were measured by fluorescence-activated cell sorting and compared between these AS-risk and protective genotypes. Results: Conditional analysis identified rs11209032 as the probable causal SNP within a 1.14 kb putative enhancer between IL23R and IL12RB2. Reduced luciferase activity was seen for the risk allele (p<0.001) and reduced H3K4me1 methylation observed in CD4+ T-cells from 'A/A' homozygotes (p=0.02). The binding of nuclear extract to the risk allele was decreased ∼3.5-fold compared with the protective allele (p<0.001). The proportion of IFN-γ+ CD4+ T-cells was increased in 'A/A' homozygotes (p=0.004), but neither IL23R nor IL12RB2 mRNA was affected. Conclusions: The rs11209032 SNP downstream of IL23R forms part of an enhancer, allelic variation of which may influence Th1-cell numbers. Homozygosity for the risk 'A' allele is associated with more IFN-γ-secreting (Th1) cells. Further work is necessary to explain the mechanisms for these important observations.